2010
DOI: 10.1021/la100467p
|View full text |Cite
|
Sign up to set email alerts
|

Selective Monovalent Cation Association and Exchange around Keplerate Polyoxometalate Macroanions in Dilute Aqueous Solutions

Abstract: The interaction between water-soluble Keplerate polyoxometalate {Mo(72)Fe(30)} macroions and small countercations is explored by laser light scattering, anomalous small-angle X-ray scattering (ASAXS), and isothermal titration calorimetry (ITC) techniques. The macroions are found to be able to select the type of associated counterions based upon the counterions' valence state and hydrated size, when multiple types of additional cations are present in solution (even among different monovalent cations). The prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 44 publications
5
68
1
5
Order By: Relevance
“…[9] Examples include inorganic molecular clusters such as polyoxometalates( POMs), [10] [a] Dr. Similar behavior was also observed for otherc olloidal systems.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…[9] Examples include inorganic molecular clusters such as polyoxometalates( POMs), [10] [a] Dr. Similar behavior was also observed for otherc olloidal systems.…”
mentioning
confidence: 65%
“…[9] All the slopes of the best-fit lines at different concentrationsw ere close to 2.5 ( Figure 1a nd Table S1). Rb + and Cs + ions can strongly bind to {Mo 72 Fe 30 }a nd precipitate them;t herefore, the data for these cations were excluded from the linear regression.…”
mentioning
confidence: 72%
“…4 Aqueous solubility and ion-pairing is extremely complex because many phenomena are involved including the lattice energy of the crystallized or precipitated solid, the hydration sphere of both the cation and anion, the sum of ions present in solution, and pH effects if the cation and/or anion is a polyatomic oxo-ion. [5][6][7] Alkali salts of polyoxometalates (POMs), the early d 0 Group V/VI metal-oxo clusters, are ideal for probing both ion-association [8][9][10][11][12] and crystal growth mechanisms, [13][14][15][16][17][18] and these two phenomena are intimately related. The large ion size and heavy metals of the POMs scatter X-rays strongly.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to synthetic and bio-polymers, ASAXS has been recently used to probe cation binding efficiency on to Keplerate polyoxometalate blackberry-like supermolecular structures [32]. This study confirmed that the less hydrated monovalent cations can bind stronger to a polyoxometalate macroion and reduce the critical salt concentration required for the formation of self-assembled colloidal structure.…”
Section: Polyelectrolytesmentioning
confidence: 58%